The Relationship of Screen Time with Body Mass Index and Sleep Quality among Freshmen at Nursing Faculty in the Pandemic of COVID-19 - Korengkeng, Loura Caroline (8ISC Abstract Proceedings, 2022)
Since announced in March 2020 in Indonesia, COVID-19 has impacted all aspects of society’s lives, including the education system. The online learning system is one of the policies set by the government in response to prevent the spread of COVID-19. Practically, students were required to spend more time in front of the screen in order to take part in-class activities such as viewing material, attending the online class meeting, and doing assignments. The purpose of this study was to figure out the relationship between screen time, Body Mass Index (BMI), and sleep quality of freshmen students at the Nursing Faculty of Klabat University during the COVID-19 pandemic. Analytical descriptive research design with a cross-sectional approach was conducted, where the population is all freshmen students of the Nursing Faculty for the academic year 2020/2021 with a total sample of 94 people taken by simple random sampling technique. The results showed that 96% of respondents spent more than 2 hours in front of the screen every day, 45% of respondents had normal BMI status, and 89% of respondents had poor sleep quality. Pearson Chi-Square statistical test results show that there is no significant relationship between screen time and BMI in freshmen students during the COVID-19 pandemic. Meanwhile, there is a significant relationship between screen time and sleep quality for the students. It is recommended for further researchers to add other variables or factors that can affect sleep quality, such as physical activity and level of academic stress, and to use more comprehensive, precise tools, especially to measure the students’ condition during the COVID-19 pandemic. Keywords : Body mass index, sleep quality, Covid-19, freshmen